Rancangan Manajemen Produk Tempe di Sidoarjo Dengan Menggunakan Metode Kualitatif - Amala Alvina Rachma; Fitri Nur Latifah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Management is a process of resources owned by a company to achieve the desired goals. According to Henry Fayol, this management has a good fuction if it applies five management functions, namely planning, organizing, directing, controlling and evaluating. Based on the facts in the field obtained from an observation, there are several problems in the implementation of production management, namely the directing function and controlling function have not been running well. This research was carried out in several Home Industries, namely Bu Khollifah Usaha, whose address is Jl. Kedung Rahmat RT. 017/ RW. 005, Krajan Hamlet, Sepande Village, Candi District, Sidoarjo Regency, Home Industry Pak Jamali Usaha, whose address is Jl. Raya Nyamplung RT. 025/ RW. 010, Sumokali Hamlet, Nyamplung Village, Candi District, Sidoarjo Regency, Home Industry Pak Ulil Usaha, whose address is Jl. Sidodadi RT. 015/ RW. 020, Sudio Hamlet, Sidodadi Village, Candi District, Sidolarjo Regency. The research method used is descriptive qualitative, namely examining the reality that occurs in the research field. In this series of research activities, descriptive data is produced in the form of written words. Based on the research results, the application of production management for the Tempe Khollifah home industry has implemented five management functions in accordance with Henry Fayol's theory. However, the implementation of production management has not run optimally because the direction and control sections have not been carried out well.